2018
DOI: 10.1186/s12983-018-0261-1
|View full text |Cite
|
Sign up to set email alerts
|

Does the early social environment prepare individuals for the future? A match-mismatch experiment in female wild cavies

Abstract: BackgroundThe social environment that mothers experience during pregnancy and lactation has a strong effect on the developing offspring. Whether offspring can be adaptively shaped to match an environment that is similar to the maternal one is still a major question in research. Our previous work in wild cavies showed that females whose mothers lived in a stable social environment with few social challenges during pregnancy and lactation (SE-daughters) developed different behavioral phenotypes than females whos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 75 publications
(79 reference statements)
0
8
0
Order By: Relevance
“…For this to be an advantageous strategy, one might expect that stress programming should optimize fitness under ancestral stress conditions. To our knowledge, this has not yet been investigated, but several studies have demonstrated that early stress actually may optimize survival skills, energy expenditure and reproductive strategies in the exposed generation (Cameron et al, 2008;Champagne et al, 2008;Sangenstedt, Szardenings, Sachser, & Kaiser, 2018). Rats that received poor maternal care as infants reach puberty earlier and engage in higher rates of sexual behavior as adults, perhaps ensuring reproductive success in uncertain conditions (Cameron et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…For this to be an advantageous strategy, one might expect that stress programming should optimize fitness under ancestral stress conditions. To our knowledge, this has not yet been investigated, but several studies have demonstrated that early stress actually may optimize survival skills, energy expenditure and reproductive strategies in the exposed generation (Cameron et al, 2008;Champagne et al, 2008;Sangenstedt, Szardenings, Sachser, & Kaiser, 2018). Rats that received poor maternal care as infants reach puberty earlier and engage in higher rates of sexual behavior as adults, perhaps ensuring reproductive success in uncertain conditions (Cameron et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This study aims to investigate whether dominance rank, baseline cortisol level, and cortisol responsiveness (here defined as the absolute cortisol concentration after 1 and 2 h of exposure to a stressor) [ 29 , 33 , 34 ] are repeatable and whether dominance rank correlates to cortisol concentrations in female guinea pigs ( Cavia aperea f. porcellus ). Guinea pigs are social mammals, and females form linear dominance hierarchies [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Videos were recorded in the afternoons For analysis, several behaviors were combined into summary categories. These categories were based on previous work with guinea pigs and cavies (Sachser & Kaiser, 1996;Sangenstedt et al, 2018).…”
Section: Social Behavior In Home Enclosurementioning
confidence: 99%